2020
DOI: 10.1002/acm2.12876
|View full text |Cite
|
Sign up to set email alerts
|

A novel dynamic robotic moving phantom system for patient‐specific quality assurance in real‐time tumor‐tracking radiotherapy

Abstract: In this study, we assess a developed novel dynamic moving phantom system that can reproduce patient three-dimensional (3D) tumor motion and patient anatomy, and perform patient-specific quality assurance (QA) of respiratory-gated radiotherapy using SyncTraX. Three patients with lung cancer were enrolled in a study. 3D printing technology was adopted to obtain individualized lung phantoms using CT images. A water-equivalent phantom (WEP) with the 3D-printed plate lung phantom was set at the tip of the robotic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…17,18 Our previous study reported a dynamic robotic phantom system that could reproduce 3D respiratory motion for the QA of motion management systems. 19 Recently, a 6DoF motion platform was developed to compensate for head movements during stereotactic radiosurgery, thus allowing for frameless and maskless treatment. 20 The geometric accuracy and reproducibility of this system were evaluated using an anthropomorphic head phantom and infrared optical tracking system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Our previous study reported a dynamic robotic phantom system that could reproduce 3D respiratory motion for the QA of motion management systems. 19 Recently, a 6DoF motion platform was developed to compensate for head movements during stereotactic radiosurgery, thus allowing for frameless and maskless treatment. 20 The geometric accuracy and reproducibility of this system were evaluated using an anthropomorphic head phantom and infrared optical tracking system.…”
Section: Introductionmentioning
confidence: 99%
“…However, most phantoms can only replicate the one‐dimensional (1D) or 2D motion of a target 17,18 . Our previous study reported a dynamic robotic phantom system that could reproduce 3D respiratory motion for the QA of motion management systems 19 …”
Section: Introductionmentioning
confidence: 99%
“…The authors reported a reproducibility of the motion traces of 0.3 mm and 0.5 deg. Shiinoki et al developed a patient-specific procedure for respiratory motion QA using a MZ07-1 robot (Nachi-Fujikoshi, Tokyo, Japan) [39]. Here, respiratory motion of the patient was recorded and a 3D printed model of the patient anatomy was placed inside a water basin.…”
Section: Robotic Quality Assurancementioning
confidence: 99%
“…We have proposed a trajectory correction algorithm using its velocity and acceleration to compensate for the network transmission lag, and showed experimentally that the tracking errors for four lung tumor trajectories fell within the clinical 1mm tolerance. It was shown to enable high precision QA for translational motion of a tumor [8]. We also developed a six DOF version of the robotic phantom by using joint level angle trajectories corrected in the same manner.…”
Section: Introductionmentioning
confidence: 99%